SCHOOL COUNSELOR'S ETHICAL DILEMMA: SCOPING REVIEW - Dwi Oktadinata; Susi Fitri; Eka Wahyuni (LP2M IAI Al-Khairat Pamekasan, 2026)
Ethical dilemmas are an inherent part of professional practice and can arise in all fields, including the role of school counselors. In the context of educational settings, school counselors are frequently confronted with complex situations that require them to balance professional responsibilities, institutional policies, and the best interests of students. However, not all counselors are fully aware that the challenges they encounter constitute ethical dilemmas, which can lead to uncertainty and inconsistency in decision-making processes. This lack of awareness may hinder their ability to respond appropriately and professionally when faced with sensitive situations. Several common ethical dilemmas experienced by school counselors include issues related to confidentiality, mandatory reporting, professional competence, boundary management, and multiple role relationships. Confidentiality, for instance, often becomes a dilemma when counselors must decide whether to maintain student privacy or disclose information for the sake of the student’s safety or well-being. Similarly, reporting obligations can create tension between ethical principles and legal requirements. Issues of competence may arise when counselors feel inadequately prepared to handle certain cases, while boundary concerns and multiple roles—such as being both a counselor and a teacher—can blur professional limits and complicate interactions with students. These dilemmas can create significant challenges for school counselors in making sound ethical decisions, particularly when clear guidelines are lacking. Therefore, this research is important as it highlights the need to identify and understand the conditions that trigger ethical dilemmas in school counseling practice. The findings are expected to provide valuable insights for policymakers and counseling practitioners to develop comprehensive ethical guidelines and support systems. Ultimately, such efforts can assist school counselors in making informed, ethical, and student-centered decisions in their professional practice.